Comparative Study of Narrow-Band Imaging and i-scan for Predicting the Histology of Intermediate-to-Large Colorectal Polyps: A Prospective, Randomized Pilot Study - Joon Seop Lee; Seong Woo Jeon; Yong Hwan Kwon (Clinical Endoscopy, 2021)
Background/Aims To date, no reports have compared the diagnostic efficacy of narrow-band imaging (NBI) and i-scan for the histologic prediction of intermediate-to-large colorectal polyps. We aimed to compare the diagnostic accuracy of NBI and i-scan in predicting histology, and their inter-/intra-observer agreement. Methods We performed a prospective, randomized study that included 66 patients (NBI, n=33 vs. i-scan, n=33) with colorectal polyps (size >10 mm but <50 mm) who underwent colonoscopic resection. During the procedure, three endoscopists documented their prediction using the Japan NBI Expert Team (JNET) classification. Two months after study completion, the endoscopists reviewed still images and video clips for analysis. Results The overall diagnostic accuracies in the NBI and i-scan groups were 73.7% (73/99) and 75.8% (75/99), respectively, and there was no statistical significance between the two groups (p=0.744). The JNET classification as applied to NBI and i-scan showed substantial inter-observer agreement (NBI κ-value 0.612, p=0.001 vs. i-scan κ-value 0.662, p=0.002). Additionally, the κ-values of intra-observer agreement were in the range of 0.385–0.660 with NBI and 0.364–0.741 with i-scan. Conclusions NBI and i-scan have similar diagnostic accuracies for the histologic prediction of intermediate-to-large colorectal polyps. Furthermore, the inter-/intra-observer agreement was acceptable for both modalities when the JNET classification was applied.